1987
DOI: 10.1007/bf02372539
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lime and phosphorus on the function of wheat roots in acid top soils and subsoils

Abstract: Two wheat varieties with differing aluminium tolerance were grown in pots of acid soil. Liming did not change significantly the amounts of chemically extractable P and K, but caused improved vegetative growth, increased inflow of P and K and reduced uptake of AI. Without lime, roots had a higher content and concentration of P than shoots; liming reversed this. Without lime the sensitive variety with a shorter root length had an AI inflow ten times that of the tolerant one: tolerance involves a mechanism for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
3
13
0
2
Order By: Relevance
“…Does P deficiency in the subsoils limit root growth? DeMiranda and Rowell (1987) found that liming subsoils improved plant growth, but yield was still limited by low P availability. Additions of P to the topsoil (presumably with adequate soil moisture) caused good growth regardless of subsoil acidity.…”
Section: Phosphorus Deficiencymentioning
confidence: 98%
“…Does P deficiency in the subsoils limit root growth? DeMiranda and Rowell (1987) found that liming subsoils improved plant growth, but yield was still limited by low P availability. Additions of P to the topsoil (presumably with adequate soil moisture) caused good growth regardless of subsoil acidity.…”
Section: Phosphorus Deficiencymentioning
confidence: 98%
“…Pellet, unpublished data). It has also been shown that the application of Pi fertilizers to surface soil horizons enhanced the ability of plant roots to penetrate the surface soil horizons and to enter acidic subsoils, where A1 concentrations limit root growth (Miranda and Rowell, 1987;McLaughlin and James, 1991). According to the authors, Al-phosphate formation was a possible cause for this beneficia1 response.…”
Section: Root Apical Pi Exudationmentioning
confidence: 99%
“…Freqüentemente, esses solos apresentam baixa disponibilidade de nutrientes, e o alumínio tóxi-co impõe restrições ao desenvolvimento das raízes, ao mesmo tempo que reduz a absorção de nutrientes (Miranda & Rowell, 1987). Em razão desse aspecto, a capacidade que as plantas forrageiras devem possuir para vegetar satisfatoriamente nessas condições, principalmente em relação às plantas daninhas que infestam essas áreas, é crucial para a manutenção da produtividade elevada da área.…”
Section: Introductionunclassified